(untitled) (World Bulletin of Public Health, 2024)
In this article, the authors cite the relevance of simulation training in medicine, in particular in the specialty therapy. At the present stage, the main burden of simulation training should be assigned to teachers of specialized departments working in clinical institutions. Optimal is the parallel work of the teacher both in the clinic and in the simulation center, which allows for high–level training.